Učinek ultravijoličnega sevanja na smreko (Picea abies (L.) Karst) in posledice za gorski gozdni ekosistem - Trošt Sedej, Tadeja (Zbornik gozdarstva in lesarstva, 2005)
Norway spruce trees from the subalpine stand are exposed not only to high UV-B radiation but also to a complex of other environmental factors, suchas high photosynthetically active radiation, extreme temperature conditions, deficient water and mineral supply, which might cause stress responses. Current year needles from the subalpine stand exhibited lower photochemical efficiency and total chlorophyll content compared to samples from lower altitudes. The result suggested that young needles were most vulnerable to stress factors, since the protective mechanisms were not fully developed. Current+1 year needles from the subalpine stand exhibited lower ETSvalues and higher total UV-B absorbing compounds, which may be interpreted as most successful protection against UVB radiation of current+1 year needles among the three needle age classes. Despite the obtained results, the effect of a single stress factor on spruce could not be easily drawn out. Still, we may assume that the spruce is quite tolerant to high UV-B radiation and other extreme environmental factors in the mountains.
Keywords: mikroklima; Picea abies; smreka; UV sevanje; vplivi